Hot Stars in Stellar Populations of Galaxies - Claus Leitherer (Galaxies)
Star-forming galaxies are hosts of dominant populations of recently formed, hot, massive stars, which give rise to conspicuous stellar spectral features and provide the ionizing fluxes. Strong outflows of these stars shape their properties. These winds affect the evolution and the output of ionizing radiation, as well as the energy and momentum input in the interstellar medium and the chemical enrichment. Many properties of massive stars become even more extreme at a low metallicity. Owing to the pioneering observations of young, metal-poor stellar populations, both locally with HST and large ground-based facilities and at high redshift with JWST, we are at a key moment to assess our understanding of hot massive stars in these galaxies. Stellar population synthesis is a key tool. I will demonstrate how population models of hot, massive stars help to address some issues at the forefront of current research. The recent advent of new evolutionary and atmosphere models of massive stars probing new parameter space allows us to characterize the properties of nearby and distant populations.